Processes of dynamical aging of steel during external friction - Шевеля, В.В.; Coкoлaн Ю.C. (Problems of Tribology, 2015)
Influence of external friction of carbon steel on substructural changes, controlling aging processes and relaxation of dynamical tensions, that define dissipative properties (energy intensity) of frictional contact was studied by temperature-dependent internal friction. It is shown, that during friction saturation of solid solution by foreign interstitial atoms, their dif-fusive activity and also quantity and morphology of exudations influence on formation of relaxational (dissipative) ability of steel. Mobility of dislocations and resistance to viscous flow on interface depends on mentioned higher, that is properties, de-fining ability of realization of aging dynamical mechanisms, accompanied by tension relaxation directly during friction.